Genome-Wide Characterization of QYYZ-Like PRRSV During 2018–2021 - Xu, Hu; Xiang, Lirun; Tang, Yan-Dong; Li, Chao; Zhao, Jing; Gong, Bangjun; Sun, Qi; Leng, Chaoliang; Peng, Jinmei; Wang, Qian; Zhou, Guohui; An, Tongqing; et al. (Frontiers in Veterinary Science, 2022)
In the last decade, the emergence of QYYZ-like porcine reproductive and respiratory syndrome virus (PRRSV) has attracted increasing attention due to the high incidence of PRRSV mutation and recombination. However, the endemic status and genomic characteristics of the QYYZ-like strains are unclear. From 2018 to October 2021, 24 QYYZ-like PRRSV isolates were obtained from 787 PRRSV-positive clinical samples. Only one QYYZ-like positive sample was from a northern province, and the rest were from central and southern provinces. We selected 9 samples for whole-genome sequencing, revealing genome lengths of 15,008-15,316 nt. We retrieved all the available whole-genome sequences of QYYZ-like PRRSVs isolated in China from 2010-2021 (n = 28) from GenBank and analyzed them together with the new whole-genome sequences (n=9). Phylogenetic tree analysis based on the ORF5 gene showed that all QYYZ-like PRRSV strains belonged to sublineage 3.5 but were clustered into three lineages (sublineage 1.8, sublineage 3.5, and sublineage 8.7) based on whole-genome sequences. Genomic sequence alignment showed that QYYZ-like strains, have characteristic amino acids insertions or deletions in the Nsp2 region (same as NADC30, JXA1 and QYYZ) and that thirteen strains also had additional amino acid deletions, mostly between 468-518 aa. Moreover, QYYZ-like strains (sublineage 3.5) have seven identical characteristic amino acid mutations in ORF5. Recombination analysis revealed that almost all QYYZ-like complete genome sequences (36/37) were products of recombination and mainly provided structural protein fragments (GP2-N) for the recombinant strains. Overall, QYYZ-like strains were mainly prevalent in central and southern China from 2018 to 2021, and these strains provided recombinant fragments in the PRRSV epidemic in China.